PENGARUH HARGA, PROMOSI, DAN KEMUDAHAN BERTRANSAKSI TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE PAYMENT GO-PAY SELAMA PANDEMI - Yolanda, Rhofita Elva; Abdullah , Mohammad Faisal (Journal of Financial Economics & Investment, 2021)
In 20220 the global society being together dealing with the Covid-19 virus which the WHO later declared this virus to be of international concern because it was considered a public health emergency. As a result, many people prefer to do activities from home, one of them is doing shopping transaction activities. In this advanced modern era, people don’t need to be difficult to leave the home to shop, because there is much application that provides online buying and selling service, one of wich is the Gojek application wich has the Go-Pay feature. this research is quantitative research using the method of multiple linear regression analysis cross-sections which was analyzed by sPSS 16.0. the result of this study indicates that simultaneously the variable of price has not significant, than promotion, and ease of transaction has a significant effect on interest in using Go-Pay mobile payments. The coefficient of determination (R2) shows that 34.4 percent f the interest in using Go-Pay mobile payments and the remaining 66.6 percent is explained by other variables not examined. When viewed partially, promotion and ease of transaction have a significant effect on interest in using Go-Pay mobile payments, while price doesn't significantly affect interest in using Go-Pay mobile payments.